2014
DOI: 10.1155/2014/594014
|View full text |Cite
|
Sign up to set email alerts
|

Genes Encoding Toxin ofClostridium difficilein Children with and without Diarrhea

Abstract: The presence of gene 16S rRNA and genes encoding toxin A (tcdA), toxin B (tcdB), and binary toxin (cdtA/cdtB) of Clostridium difficile in stool samples from children with (110) and without (150) diarrhea was determined by using a TaqMan system. Fifty-seven (21.9%) out of 260 stool samples harbored the 16S rRNA gene. The genetic profile of tcdA+/tcdB− and cdtA+/cdtB+ was verified in one C. difficile-positive diarrhea sample and of tcdA+/tcdB+ in three C. difficile-positive nondiarrhea samples. The presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Nonetheless, contemporaneous studies have reported higher rates (up to 30%) of asymptomatic colonization among noninfant pediatric populations (111,118,119). Similarly, Merino and colleagues found that around a quarter of U.S. children aged 1 to 5 years were colonized asymptomatically by C. difficile (120). By using a molecular identification method to classify groups by the presence of the toxin A gene (tcdA), the toxin B gene (tcdB), and the binary toxin genes (cdtA/B), they found that although 3/37 asymptomatically colonized children harbored a strain with the toxigenic genes (tcdA and tcdB), none carried the binary toxin genes (cdtA/cdtB).…”
Section: Children (2 To 16 Years)mentioning
confidence: 91%
“…Nonetheless, contemporaneous studies have reported higher rates (up to 30%) of asymptomatic colonization among noninfant pediatric populations (111,118,119). Similarly, Merino and colleagues found that around a quarter of U.S. children aged 1 to 5 years were colonized asymptomatically by C. difficile (120). By using a molecular identification method to classify groups by the presence of the toxin A gene (tcdA), the toxin B gene (tcdB), and the binary toxin genes (cdtA/B), they found that although 3/37 asymptomatically colonized children harbored a strain with the toxigenic genes (tcdA and tcdB), none carried the binary toxin genes (cdtA/cdtB).…”
Section: Children (2 To 16 Years)mentioning
confidence: 91%
“…Real‐time PCR was carried out on a 7500 Fast Real‐time PCR System (Thermo Fisher Scientific, Waltham, MA, USA) using the Fast SYBR ® Green Master Mix (Thermo Fisher Scientific, Waltham, MA, USA), following manufacturer’s instructions. We examined the expression of toxin A, B, and binary toxin by real‐time PCR using tcdA (Lyras et al ), tcdB (Lyras et al ), cdtA (Merino et al ), cdtB (Merino et al ), rpoA (Lyras et al ) and 16SrRNA (Buffie et al ) primers.…”
Section: Methodsmentioning
confidence: 99%
“…[8,[25][26][27][28][29] The presence of A + B -strains though rare in literature was reported earlier by some authors. [8,27] Analysis of clinical spectrum of the PCR positive patients was also attempted as a part of the study. The clinical features and risk factors usually encountered in patients with toxigenic C. difficile were observed in our patients also.…”
Section: Resultsmentioning
confidence: 80%